Technical and vocational education and training in sub-Saharan Africa: a comprehensive review of the current state of the research (AfriTVET) - Kigwilu Changilwa, Peter; Haßler, Björn; Marsden, Melissa; Watson, Joseph; Schaffer, Jens; Kagambega, Asseta; Iseje, Fatuma; Maseko, Vusi; Orji, Chibueze Tobias; Deodonne, Kunwufine; Amina, Idris; Ewnetu, Tamene; et al. (AfriTVET International Conference, RVTTI, Kenya, June 2019, 2019)
Research funded by Federal Ministry for Research and Education, Germany
Keywords: Author:Haßler; Author:OpenDevEd